Angiomotin is a novel component of cadherin‐11/β‐catenin/p120 complex and is critical for cadherin‐11‐mediated cell migration. Issue 3 (2nd December 2014) - Ortiz, Angelica; Lee, Yu‐Chen; Yu, Guoyu; Liu, Hsuan‐Chen; Lin, Song‐Chang; Bilen, Melmet Asim; Cho, Hyojin; Yu‐Lee, Li‐Yuan; Lin, Sue‐Hwa
Abstract : Loss of E‐cadherin and up‐regulation of mesenchymal cadherins, a hallmark of the epithelial–mesenchymal transition, contributes to migration and dissemination of cancer cells. Expression of human cadherin‐11 (Cad11), also known as osteoblast cadherin, in prostate cancer increases the migration of prostate cancer cells. How Cad11 mediates cell migration is unknown. Using the human Cad11 cytoplasmic domain in pulldown assays, we identified human angiomotin (Amot), known to be involved in cell polarity, migration, and Hippo pathway, as a component of the Cad11 protein complex. Deletion analysis showed that the last C‐terminal 10 amino acids in Cad11 cytoplasmic domain are required for Amot binding. Further, Cad11 preferentially interacts with Amot‐p80 than Amot‐p130 isoform and binds directly to the middle domain of Amot‐p80. Cad11‐Amot interaction affects Cad11‐mediated cell migration, but not homophilic adhesion, as deletion of Amot binding motif of Cad11 (Cad11‐Δ Amot) did not abolish Cad11‐mediated cell–cell adhesion of mouse L cells, but significantly reduced Cad11‐mediated cell migration of human C4‐2B4 and PC3‐mm2 prostate cancer cells and human HEK293T cells. Together, our studies identified Amot‐p80 as a novel component of the Cad11 complex and demonstrated that Amot‐p80 is critical for Cad11‐mediated cell migration.—Ortiz, A., Lee, Y.‐C., Yu, G., Liu, H.‐C., Lin, S.‐C., Bilen, M. A., Cho, H., Yu‐Lee, L.‐Y., Lin, S.‐H. Angiomotin is a novel component of cadherin‐11/β‐catenin/p120 complex and is critical for cadherin‐11‐mediated cell migration. FASEB J. 29, 1080–1091 (2015). www.fasebj.org